From The jungle to HACCP: A first-hand view of the United States meat inspection process - Bradburn, Ryan (My University, 2008)
Since the advent as the Bureau of Animal Industry in 1884, the United States Department of Agriculture (USDA) has had an evolving role working to protect the U.S. food supply. The agency’s role in food safety was redefined by the Federal Meat Inspection Act of 1906; and toward the end of the 20th century it replaced its organoleptic approach to inspection with Hazard Analysis and Critical Control Points (HACCP), a much more modern and scientific approach. This summer, I had the chance to experience the USDA Food Safety and inspection Service (FSIS) from the inside, across the gamut of its responsibilities. These responsibilities have not only grown, but their importance has become increasingly evident over the agency’s history. Scrutiny dominated by public opinion, which in turn is often influenced by casuistic reasoning, compounds the complexity of the duties of the FSIS. In the end, the FSIS is an extension of the executive branch of the federal government – a service of, by, and for the nation’s citizens. This summer has granted me a great deal of experience and knowledge regarding food safety in the United States, especially as it relates to the meat industry. I have been able to see the breadth of the jurisdiction of the FSIS, observing small slaughter operations, as well as highspeed pork, poultry, and beef establishments. I have seen new and old processing facilities, an egg powdering plant, and have been challenged to fill the shoes of an Enforcement Investigative and Analysis Officer (EIAO) for a day. The provision of food safety for a nation’s food supply is an arduous task requiring a monumental amount of paperwork. The implementation of HACCP has placed responsibility on plants to create a safe product, and has provided a scientific model for them to use. This scientific basis has led to tighter controls and safer product, but can be difficult for smaller establishments to research and evaluate. Nonetheless, food safety plays a vital role in public health and the FSIS is an integral part of that process, impacting the food supply not only of the United States, but the world as well.
This field experience report was presented by Ryan Bradburn in partial fulfillment of the requirements for the degree Master of Public Health.
Keywords: HACCP; Meat inspection; Public health; Food safety; USDA